Elaboración de dos tipos de té a partir de hojas de moringa oleifera combinado con lippia alba y cymbopogon citratus. - Cruz Alvia, Cinthia Mabel; Cunalata Cueva, Gabriela Viviana (Machala : Universidad Técnica de Machala, 2019)
The research work that occupies uses three plant species of wide traditional use. Moringa oleifera Lam is a medicinal plant that with pharmacological, nutritional properties. Cymbopogon citratus is a species that is used for medicinal purposes, likewise, Lippia alba Mill is an aromatic shrub, where its leaves are used in infusion for gastrointestinal treatments. The objective of the research was to develop two formulations to prepare as infusions, using leaves of M. oleifera as the main active ingredient, combined with leaves of L. alba and C. citratus; to obtain a drink that helps to improve the physiological functions in the organism, preventing the risk to certain diseases. The corresponding physical-chemical tests were carried out on the drugs of the three species under study, obtaining a residual humidity of 6.42% for M. oleifera; 8.70% for C. citratus and 10.91% for L. alba; total ashes of 10.41%; 8.64% and 11.19%, respectively, and insoluble ashes in 10% HCl, decreasing the values to 1.94%; 4.71% and 6.94%, respectively. Given the high concentration of inorganic matter, the presence of the heavy metals Arsenic and Lead in the three drugs was ruled out, resulting in the three levels not exceeding the limits established in the INEN 2392-2010 standard. The study of quantification of the minerals allowed to know the contribution of macrominerals and microminerals of the three species, resulting, the L. alba with the highest values, in particular that of the Fe mineral with 7459 p.p.m.
El trabajo de investigación que ocupa utiliza tres especies vegetales de amplio uso tradicional. Moringa oleifera Lam es una planta medicinal que posee propiedades farmacológicas, nutritivas. Cymbopogon citratus es una especie que se utiliza con fines medicinales, de igual manera, Lippia alba Mill es un arbusto aromático, donde sus hojas se utilizan en infusión para tratamientos gastrointestinales. El objetivo de la investigación fue elaborar dos formulaciones para preparar como infusiones, usando hojas de M. oleifera como principal ingrediente activo, combinadas con hojas de L. alba y C. citratus; para obtener una bebida que ayude a mejorar las funciones fisiológicas en el organismo, previniendo el riesgo a determinadas enfermedades. Se realizaron los correspondientes ensayos físicos-químicos a las drogas de las tres especies en estudio, obteniéndose una humedad residual de 6,42% para M. oleifera; 8,70% para C. citratus y 10,91% para L. alba; cenizas totales de 10,41%; 8,64% y 11,19%, respectivamente y cenizas insolubles en HCl al 10%, disminuyendo los valores a 1,94%; 4,71% y 6,94%, respectivamente. Dada la elevada concentración de materia inorgánica se procedió a descartar la presencia de los metales pesados Arsénico y Plomo en las tres drogas, dando como resultado que en los tres casos los niveles no superaron los límites establecidos en la norma INEN 2392-2010. El estudio de cuantificación de los minerales permitió conocer el aporte de macrominerales y microminerales de las tres especies, resultando, la L. alba con los valores más altos, en particular el del mineral Fe con 745,9 p.p.m.